The Impact of Parental Role Distributions, Work Participation, and Stress Factors on Family Health-Related Outcomes: Study Protocol of the Prospective Multi-Method Cohort “Dresden Study on Parenting, Work, and Mental Health” (DREAM) - Kress, Victoria; Steudte-Schmiedgen, Susann; Kopp, Marie; Förster, Anke; Altus, Caroline; Schier, Caroline; Wimberger, Pauline; Kirschbaum, Clemens; von Soest, Tilmann; Weidner, Kerstin; Junge-Hoffmeister, Juliane; Garthus-Niegel, Susan (Frontiers in Psychology, 2019)
The Dresden Study on Parenting, Work, and Mental Health (“DResdner Studie zu Elternschaft, Arbeit und Mentaler Gesundheit“, DREAM) aims to prospectively investigate the relationship between parental work participation, role distribution, stress factors, and their effects on perinatal outcomes and long-term family mental and somatic health in a community sample targeting N = 4,000 individuals, i.e., 2,000 couples, expecting a child and residing in Dresden, Germany (interim sample of N = 1,410 participants, recruitment ongoing). Various questionnaires are completed at four measurement points from pregnancy to two years postpartum (prolongation into middle childhood planned). Applying a multi-method approach, long-term endocrinological data (analyses of hair cortisol concentrations and other endogenous hormones, “DREAMHAIR”) and qualitative interview data (regarding gender role attitudes and distribution of domestic work, child care, and paid employment; “DREAMTALK”) are obtained. In this study protocol, the theoretical background, methods, and preliminary results considering sociodemographic characteristics during pregnancy and birth-related factors at eight weeks postpartum are presented. Additionally, there is a focus on our endocrinological sub-study DREAMHAIR. In this sub-study currently comprising N = 152 participants, i.e., 88 families (recruitment ongoing), we want to gain knowledge on the transgenerational processes of stress regulation and psychopathology in the whole family by analyzing hair cortisol concentrations in both parents and children during the course from pregnancy (or after birth regarding children) to at least two years postpartum. By comparing data of the community sample to a clinical sample of mothers with postpartum mental disorders, their children, and their partners during the period between admission and discharge from a mother-baby unit and post-treatment (“DREAMMBU”), the course of mothers’ psychopathology, parent-infant interaction, and infant regulation disorders with special regard to long-term endocrinological correlates will be examined. With previous studies neglecting the fathers or partners involved, a major advantage of DREAM is the use of a multi-method and multi-level approach by examining the whole family in a longitudinal design. Therefore, the DREAM study will contribute to a better understanding of the role of social, work, and stress factors for mental and somatic health and its long-term endocrinological correlates in the natural course of becoming a family.